The Origins and Symbolism of Vaiśravaṇa Iconography and the Impact of the Royal Image as Donor and Protector - Yeoung Shin Shim (Religions)
This study examines the origins and symbolic meanings of the iconography of Vaiśravaṇa, which gained prominence in East Asia during the 200 years after the 8th century, through the lens of royal imagery as both a devotee and protector. As Vaiśravaṇa’s iconography spread along the Silk Road, it integrated diverse cultural traditions from the ancient Near East and the Indo-Iranian world, with Gandhāra and Khotan as central hubs. The iconography evolved into a distinctive form, featuring a cylindrical crown adorned with bird motifs, shoulder flames, a cross belt, a Stūpa, a spear, and celestial maidens. Previous studies often limited its origin to either Gandhāra or Khotan; however, this research highlights contributions from both regions, emphasizing their roles in shaping iconography. By focusing on Gandhāra and the Kushan Empire, this study explores how these elements reflect the diversity of regional cultures, political ideals, and religious values. It contextualizes these developments within historical and cultural exchanges between regions, offering a broader understanding of Vaiśravaṇa’s formation. The findings reveal that Vaiśravaṇa’s iconography reflects cultural exchange and symbolizes the sacred earthly ruler. This perspective highlights how regional diversity and intercultural interactions shaped its development, enriching the study of Buddhist iconography.